2000
DOI: 10.1161/01.hyp.35.1.507
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Action Is Associated With Endothelial Function in Hypertension and Type 2 Diabetes

Abstract: Abstract-A primary defect in the vascular action of insulin may be a key intermediate mechanism that links endothelial dysfunction with reduced insulin-mediated cellular glucose uptake in metabolic and cardiovascular disorders. The present study was designed to characterize more fully the relations between insulin action and endothelial function in male patients with essential hypertension (H, nϭ9) or type 2 diabetes (D, nϭ9) along with healthy control subjects (C) matched for age, body mass index, and lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 24 publications
4
51
0
7
Order By: Relevance
“…The Type II diabetic patients showed a lower plasma NOx concentration than non-diabetic subjects (23.9±8.2 vs 42.3±31.5 µmol/l, p=0.00003). There is increasing evidence that NO synthesis and the vasodilating properties of insulin are impaired in insulin resistant states, such as Type II diabetes and obesity [31,32]. Thus, our data agree with previous findings [33].…”
Section: Discussionsupporting
confidence: 93%
“…The Type II diabetic patients showed a lower plasma NOx concentration than non-diabetic subjects (23.9±8.2 vs 42.3±31.5 µmol/l, p=0.00003). There is increasing evidence that NO synthesis and the vasodilating properties of insulin are impaired in insulin resistant states, such as Type II diabetes and obesity [31,32]. Thus, our data agree with previous findings [33].…”
Section: Discussionsupporting
confidence: 93%
“…Our LBF data are consistent with an impaired vasodilatory response to exercise in individuals with type 2 diabetes and may relate to both vascular endothelium-dependent (52) and -independent (53) mechanisms. Lipid abnormalities, defects in the vascular action of insulin (52), and elevated blood glucose (54) all are likely contributors to impaired vascular control during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the findings shown in the relationship between age and type II diabetes, 1 supporting the concept that underlying mechanisms of hypertension and type II diabetes Gamma-glutamyltransferase, age, and hypertension D-H Lee et al are closely related, which was suggested by other studies. [12][13][14][15] Although GGT has been used clinically as a marker of alcohol consumption or liver disease, GGT plays an important role in antioxidant systems at a cellular level. [5][6][7] The maintenance of intracellular levels of glutathione is critical for antioxidant defence mechanisms of the cell, but intact extracellular glutathione is poorly transported across cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recent studies suggest that excessive production of reactive oxygen species, outstripping endogenous antioxidant defence mechanisms, may be involved in the pathogenesis and complications of both conditions. [13][14][15] Therefore, the interaction between age and serum GGT level might be interpreted as a synergic action of two markers of oxidative stress. Alternatively, we are interested in the possibility that body iron storage plays a role in this interaction between GGT and age, because the cellular role of GGT differs depending on iron storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation